2009
DOI: 10.1128/aem.01025-09
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Resistance of Nosema ceranae , a Parasite of the Honeybee, to Temperature and Desiccation

Abstract: Resistance of Nosema ceranae to different exposure conditions has been evaluated by using Sytox green and DAPI (4,6-diamidino-2-phenylindole) to test spore viability. High thermotolerance at 60 and 35°C and resistance to desiccation were observed. However, a significant decrease in viability after freezing and a rapid degeneration of spores maintained at 4°C were also detected.Two Nosema species have been related to pathology in the honeybee: Nosema apis (18) a parasite of Apis mellifera, the western honeybee,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 16 publications
3
74
0
1
Order By: Relevance
“…In the field, N. ceranae causes an unusual form of nosemosis, which led, and still leads, to severe colony losses in Spain (28,37). One explanation for the higher virulence of N. ceranae in the field could be the better adaptation of N. ceranae than of N. apis to elevated temperatures (18,36), indicating that N. ceranae might be a pathogen whose spread and assertiveness could be influenced by climate change.…”
mentioning
confidence: 99%
“…In the field, N. ceranae causes an unusual form of nosemosis, which led, and still leads, to severe colony losses in Spain (28,37). One explanation for the higher virulence of N. ceranae in the field could be the better adaptation of N. ceranae than of N. apis to elevated temperatures (18,36), indicating that N. ceranae might be a pathogen whose spread and assertiveness could be influenced by climate change.…”
mentioning
confidence: 99%
“…The development of N. ceranae is highly determined by the temperature. This species is less resistant to low temperatures than N. apis (Fenoy et al, 2009;Fries, 2010;Gisder et al, 2010;Chen et al, 2012). Considering this fact, we expected the distribution of N. ceranae in our climate to be similar to those levels identified for cooler regions Forsgren and Fries, 2013;Meixner et al, 2014).…”
Section: Epidemiological Situationmentioning
confidence: 56%
“…A recent study tested the survival capability of N. ceranae in different extreme temperature and desiccation settings (Fenoy et al 2009). The authors found that compared to control spores that were kept at 4°C, about 90 % of N .ceranae spores heated at 60°C for 6 h remained viable.…”
Section: Discussionmentioning
confidence: 99%